Disease Pattern and Outcome of Pediatric Patients Admitted in A Non-Government Medical College Hospital (IAHS Medical Journal, 2022)
Background: An understanding of epidemiological trend in hospital admissions, including diseases and death pattern, is essential for health care planning, appropriate resource allocation and improving existing services facilities. Most of the causes of morbidity and mortality in Pediatric patient particularly under five and neonate are preventable by proper antenatal/perinatal care, early detection and management. To assess the disease pattern and outcome of pediatric patients admitted in a non-government Medical College hospital this research was performed.Materials and methods: This retrospective observational study was conducted at the Department of Child Health, Marine City Medical College Hospital (MCMCH) Chattogram, Bangladesh during 2019 June to 2021 June. A total of 567 patients were included for the study. Details on demographic characteristic, disease pattern, outcome, retrieved from the medical records and admission registers, and tabulated and analyzed using Microsoft Excel (Microsoft Office20 16).Results: Among the admitted patient 0-